Consistency and variability of kinematic parameters in the triple jump - Coh, M.; Stuhec, S.; Verti, R. (New Studies in Athletics, 2011)
The purpose of the study was to examine the consistency and variability of kinematical parameters in the technique used in the triple jump, one of the most complex athletics disciplines. An examination was made of two attempts of an elite female jumper that were performed in laboratory conditions during her preparation for the 2008 Olympic Games, where she placed 6th in the final.